PENGARUH PROFITABILITAS, UMUR PERUSAHAAN DAN FINANCIAL LEVERAGE TERHADAP UNDERPRICING SAHAM INITIAL PUBLIC OFFERING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019- 2022 - Setyorini, Ani; Darmayanti, Novi; Rachmaniyah, Fatichatur (J-MACC : journal of management and accounting, 2024)
Current business progress and developments make it easy for people to recognize various investments, one of which is stocks. Investors can find out several terms in purchasing shares, one of which is the initial public offering (IPO) which is used by companies to obtain additional capital obtained from investors. This study aims to determine the effect of profitability, firm age and financial leverage on the underpricing of Initial Public Offering shares. Using a quantitative research method using a sample of 21 companies that experienced stock underpricing in 2019-2022. The data analysis technique in this study used multiple linear regression analysis using SPSS version 26. This research tested using the t test and F test. The results of this study indicate that partially profitability, firm age and financial leverage have a significant effect on initial public offering stock underpricing. Simultaneously profitability, firm age and financial leverage have a significant effect on initial public offering stock underpricing.